INVESTIGATING STUDENTS’ THINKING PROCESSES DURING GROUP PRESENTATIONS AT A UNIVERSITY IN RIAU - Amelia, Riza (Journal of English and Arabic Language Teaching, 2025)
Investigating thinking processes during classroom group presentations can help identify their needs for appropriate guidance on how to deliver a presentation. Therefore, this study investigates the students’ thinking processes during the pre-presentation, presentation, and post-presentation stages in a course conducted in Bahasa Indonesia. Within this context, the participants were asked to describe their thinking processes. The research employed a qualitative descriptive design and involved ten student participants—two males and eight females. Presentations were conducted in one semester, whereas data collection of students’ thinking processes taking place at the end. The instruments used included observations, closed-ended questions, and open-ended questions. The data were analyzed using thematic analysis. Triangulation of different data sources was applied to ensure data validity. The findings identified three main stages of thinking: pre-presentation, during-presentation, and post-presentation that are consistent with Flavel (1979) and Zimmerman (2000) theories. Within each stage, the students reported experiencing complex thoughts while also facing challenges related to cognition, psychological factors, and social interaction. Based on the findings, future studies are recommended to explore topics such as the effectiveness of classroom group presentation training and the development of communication skills through presentations.